Successful polyploidy induction and detection in blackberry species by using an in vitro protocol - Sabooni, N.; Gharaghani, A.; Jowkar, A.; Eshghi, S.
Blackberries are widely used as a fresh fruit, while being highlighted as an anti-inflammatory and antioxidant source. Polyploidization is considered as a valuable and fast breeding method to develop new cultivars with enhanced characteristics. In this research, a procedure was adapted in vitro to generate polyploid plants (3x, 4x, 6x and 8x)in seven genotypes assigned to five blackberry species, including Rubus sanctus (3 genotypes), R. hirtus, R. caecious, R. persicus and R. discolor. Nodal segments were cultured in Murashige and Skoog media supplemented with oryzalin (0, 125, 250 and 375 mgL?1)or colchicine (0, 5, 10 and 15 mgL?1)for different durations (24, 48, 72 and 96 h). Results of cytological analysis showed no significant differences between the ultimate effects of the two anti-mitotic agents (i.e. colchicine and oryzalin), whereas each species reacted differently to polyploidy induction. The best result was obtained in the R. sanctus genotype F (Sari), using 10 mgL?1 oryzalin for 48 h. Manipulative treatments led to the release of octaploid blackberry for the first time. A morphometric analysis of plant leaves showed that polyploidy affected the guard cells, increased the cell size and reduced cell count. The greenness, petiole length and chlorophyll content of leaves were significantly higher in the hexaploid R. sanctus genotype C (Lahijan), while the thickness and size of leaves were significantly larger and the spine length was significantly longer in the octaploid R. persicus. The developed in vitro procedure for polyploidy induction and detection is feasible and could be used as a promising tool to create blackberry cultivars with enhanced fruit characteristics, along with possible resistance to environmental stress.
Keywords: RUBUS; COLCHICINE; ORYZALIN; FLOW CYTOMETRY; MORPHOLOGY; CHROMOSOME COUNTING